Implications of pasture improvement for bird conservation in the high plains of the Colombian Llanos - Palacio, Ruben Dario (Resilience Alliance, Inc., 2024)
The high plains of the Colombian Llanos are emerging as a new agricultural frontier, where native tropical savannas are increasingly being converted into improved pastures to facilitate grazing intensification. However, the impacts of this land conversion have not been adequately addressed, especially in the context of biodiversity conservation. In this study, I conducted bird surveys at Hacienda San José (HSJ), a private cattle farm that established improved pastures with a focus on sustainable intensification while preserving an area of native savanna vegetation. I evaluated bird density, species richness, and community similarity across three land-use management regimes: improved pastures with rotational grazing and burning exclusion (IP), preserved native savanna with no burning or grazing (PNS), and conventionally managed savanna (CMS) subject to burning and grazing, located outside of HSJ. Results showed that IP had the highest bird species richness and density. However, PNS and CMS supported unique populations of savanna specialist birds at higher abundances, while CMS had the lowest overall species diversity of the three management regimes. These findings (1) highlight the importance of preserving native savanna vegetation within agricultural landscapes of the Colombian Llanos and (2) suggest that improved pastures, coupled with sustainable management practices, can help sustain a diverse savanna bird community. Future land use intensification projects should maintain a range of different habitats alongside production areas to ensure the persistence of both generalist and savanna specialist birds in this relatively understudied region of Colombia.